REGIONAL LANGUAGE EXCLUSION IN DIGITAL LEARNING: THE IMPACT OF LANGUAGE POLICY ON EDUCATION ACCESS IN REMOTE AREAS - Nurlaeli, Nisa; Jaja, Jaja; Susilo, Jimat (JURNAL KONFIKS, 2025)
This research aims to examine various forms of regional language exclusion in the context of digital learning and its implications for language policy and access to education in remote areas. The approach employed is library research, involving a thorough review of various scientific journals, books, and relevant policy documents from the past decade. The study's findings indicate that regional language exclusion is reflected in several aspects, including the unavailability of learning content in local languages, a lack of teacher training related to the use of local languages, and centrally designed curricula that do not consider local linguistic diversity. This has resulted in increasing educational inequality, especially in 3T areas, where students struggle to understand the material due to the language of instruction being different from their mother tongue. This research reinforces the sociocultural constructivist perspective and a multilocal literacy approach, demonstrating a strong relationship between linguistic exclusion and disparities in access to digital education. The absence of regional languages in digital learning has broader implications, not only for students' understanding but also for their cultural identity and participation in learning. As a form of solution, this research recommends the implementation of culturally and contextually based digital learning strategies, such as the creation of bilingual content, teacher training in translingual approaches, and flexible and responsive educational policies to linguistic diversity. The integration of regional languages into digital systems is believed to create a fairer, more inclusive, and relevant education. The main contribution of this research lies in strengthening the direction of policies and educational practices that prioritize social and cultural justice in the digital era.